Managing virus diseases in citrus: Leveraging high-throughput sequencing for versatile applications - Hongming Chen; Zhiyou Xuan; Lu Yang; Song Zhang; Mengji Cao (Horticultural Plant Journal)
In this review, the advantages and advances in applying high-throughput sequencing (HTS) in the management of viral diseases in citrus, along with some challenges, are discussed to provide perspectives on future prospects. Since the initial implementation of HTS in citrus virology, a substantial number of citrus viruses have been identified, with a notable increase in the last 7 years. The acquisition of viral genomes and various HTS-based omics analyses serve as crucial pillars for advancing research in the etiology, epidemiology, pathology, evolution, ecology, and biotechnology of citrus viruses. HTS has notably contributed to disease diagnosis, such as the diagnoses of concave gum and impietratura, as well as to the surveillance of new virus risks and the preparation of virus-free materials. However, certain inherent defects in HTS and coupled bioinformatics analysis, such as challenges with sequence assembly and the detection of viral dark matter, require improvement to enhance practical efficiency. In addition, the utilization of HTS for the systematic management of citrus viral diseases remains limited, and drawing insights from other virus–plant pathosystems while integrating emerging compatible techniques and ideas may broaden its specific applications.